(untitled) (Medical Forum Monthly, 2024)
Objective: To find out the incidence of thyroid ima artery in our population Study Design: An exploratory study. Place and Duration of Study: This study was conducted in a private hospital and Nishtar Hospital Multan.Study was conducted from 15 Jan to 25 september 2012. Materials and Methods: All the patients with the goiter and who were euthyroid presenting to the Nishatr Hospital and private hospital (Khursheed Rafiq Hospital) in Multan were included in study.Patients with tumors and huge retrosternal goiter were excluded from the study.During surgery of thyroid, meticulous dissection was done to identify the thyroid ima artery and incidence was recorded. Results: A total no of 87 patients were included in the study. Out these 7 were excluded due to the huge goiter with difficult surgery. Out of remaining 80 pts,65(80%) were females on 15(20%) were females.(ratio of female to male ( 4.3 : 1).The mean age of the patients was 45 years (from 70 years to 20 years) The thyroid ima artery was found in 4 pts only (5%).All the patients were females It means that incidence of this artery in females is more than males.It may be due to the more incidence of goiter in females (80%) than males as this study was conducted only patients suffering from goiter. In both patients this artery was supplying the isthmus of the thyroid gland. This was of adequate size. Inferior thyroid artery was also present in both cases. Conclusion: The incidence of thyroid ima artery was recorded to be 4% in our population.